2020
DOI: 10.1111/jvh.13337
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world utility of HCV core antigen as an alternative to HCV RNA testing: Implications for viral load and genotype

Abstract: Following positive serology, the gold standard confirmatory test of hepatitis C virus (HCV) infection is detection of HCV RNA by PCR. We assessed the utility of HCV core antigen testing to identify active infection among those positive for anti‐HCV antibodies, when introduced to routine testing. We identified serum samples that were tested at a single laboratory in Scotland from June 2011to December 2017. Serum samples testing positive for HCV antibodies (HCV Ab positive) followed by reflex HCV core antigen (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although the low level of viremia may lead to reduced sensitivity of the HCV‐cAg assay, 26,28 several studies reported that HCV genotype 3 infection was associated with increased odds of a false‐negative result (odds ratio = 3.59, 95% CI: 1.32‐9.71), 28–30 which may be contributed by HCV core mutations (A48T and T49A/P) 31 . Moreover, HCV genotypes may affect HCV‐cAg levels; HCV 1b genotype may have higher HCV‐cAg levels than 3b, 2, and 1b/3b‐mix genotypes 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the low level of viremia may lead to reduced sensitivity of the HCV‐cAg assay, 26,28 several studies reported that HCV genotype 3 infection was associated with increased odds of a false‐negative result (odds ratio = 3.59, 95% CI: 1.32‐9.71), 28–30 which may be contributed by HCV core mutations (A48T and T49A/P) 31 . Moreover, HCV genotypes may affect HCV‐cAg levels; HCV 1b genotype may have higher HCV‐cAg levels than 3b, 2, and 1b/3b‐mix genotypes 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 3 has found to be associated with increased odds of a false-negative result (odds ratio(OR) = 3.59, 95% CI: 1.32-9.71), while older age (OR = 0.92, 95% CI: 0.88-0.97 per year) and VL (OR = 0.10, 95% CI: 0.05-0.21 perlog 10 IU/mL) were associated with reduced odds of a false negative. 24 Although HCV-cAg testing apply to diagnosis could lead to significant cost savings in national screening programmes, a significant proportion of HCVinfected individuals may be missed particularly in low-and middleincome regions, where genotype 3 is prevalent. These findings have implications for HCV diagnosis and determination of viral clearance after treatment.…”
Section: Hcv-cag Expression Highly Agreement With That Of Hcv-rnamentioning
confidence: 99%
“…The real-world utility of HCV cAg detection as a substitute for HCV RNA confirmation to identify active infection was demonstrated in a cohort of 744 patients in a Scottish study [ 113 ]. The overall HCV cAg assay sensitivity was demonstrated to be 82.1% and the specificity was 99.8%.…”
Section: The Real-world Clinical Performance Of Current Hcv Diagnostic Algorithmsmentioning
confidence: 99%
“…Although HCV cAg has been implemented as a cost-effective single-step HCV diagnosis strategy in high-income countries in less prevalent HCV settings, a lot of HCV-positive individuals can be missed. Due to this, HCV cAg testing could be feasible for viral clearance determination after post-HCV treatment in LMICs where GT-3 is more prevalent [ 113 ].…”
Section: The Real-world Clinical Performance Of Current Hcv Diagnostic Algorithmsmentioning
confidence: 99%